H.I.V.E. : rogue / 5 - Walden, Mark (H.I.V.E., 2011)
Doctor Nero, forced to take temporary control of G.L.O.V.E. when Diabolus Darkdoom is seriously injured, issues a capture or kill order for Otto, and Wing persuades Raven to let him help her retrieve Otto.